STUDI AWAL FABRIKASI SEL SURYA BERBASIS DYE SENSITIZED SOLAR SEL (DSSC) DENGAN MENGGUNAKAN EKSTRAK BUAH DAN DAUN SIRSAK (ANNONA MURICATA L) SEBAGAI FOTOSENSITIZER - Afandi, Irwan; Iswadi, Iswadi; Aisyah, Aisyah; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2019)
Dye sensitized solar cell (DSSC) is one type of solar cell base on organic dyies. There are many dye is from extract of plants (leave, fruit and grass) are potential as dye sensitized. In this research, the extract is come from fruit and Leaf of soursop (annona muricata L). This study aims to find great efficiency resulting from the use of extracts of the fruit and leaves of the soursop base DSSCs solar cells. The deposition method are used in this research is the Doctor blade method. Based on the results obtained from this study, DSSC efficiency of the use of soursop leaf extract is equal to 0.00104% with dye absorption spectrum in the UV region of the range 241 nm - 399.5 nm while for Visible area 502.5 nm - 664.5 nm, absorption is highest wavelength at 290 nm with the absorbance of 5.373. As for the sample of soursop fruit is in the amount of 0.005832% with dye absorption spectrum is found only in the UV region of the range of 245.5 nm - 289.5 nm, the wavelength of absorption is highest at 289.5 nm with the absorbance of 5.434. The efficiency of the dye higher soursop fruit extract from the leaves of the soursop.